May There Exist Healthy Diseases? - Manfred, Doepp (Jour Med Resh and Health Sci, 2022)
The curious question in the title seems unusual, but it is important in the future if we are not to face a multitude of undiagnosable diseases. Healthy diseases are those that detoxify and deacidify the organism, such as short acute inflammations (e.g. rhinitis, cystitis, but also eczema). Sick diseases are those that poison and overacidify the organism. They are mainly chronic-smoldering inflammations of the silent inflammation type. It is to be feared that in the future half of mankind will die from it.